2012
DOI: 10.1177/1541204012438421
|View full text |Cite
|
Sign up to set email alerts
|

Race, Probation Violations, and Structured Secure Detention Decision Making in Three Jurisdictions

Abstract: The relationships between race and probation violations with preadjudication secure detention decision and detention hearings are examined in three jurisdictions in a Midwestern state that use a detention screening instrument. Interpretations of consensus theory and the racial or symbolic threat thesis with an emphasis on race stereotyping serve as the theoretical background for the study. The results reveal race to be influential in detention decisions in one jurisdiction, while involvement in probation viola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…It is important to note that participants who had information indicating the youth was of a moderate risk level were not influenced by their emotions or the offender's race. This supports other researchers and activists, who argue that the presence of risk information appears to reduce the impact of biasing emotion and offender race effects (Leiber & Boggess, ). Our results support the increased use of standardized risk assessments in juvenile case judgments by judges, attorneys, and probation officers.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…It is important to note that participants who had information indicating the youth was of a moderate risk level were not influenced by their emotions or the offender's race. This supports other researchers and activists, who argue that the presence of risk information appears to reduce the impact of biasing emotion and offender race effects (Leiber & Boggess, ). Our results support the increased use of standardized risk assessments in juvenile case judgments by judges, attorneys, and probation officers.…”
Section: Introductionsupporting
confidence: 87%
“…Recently, advocates for juvenile justice reform have encouraged the utilization of standardized risk assessment measures (Vincent, Guy, Perrault, & Gershenson, ). Indeed, several research agencies, such as the National Research Council, Annie E. Casey Foundation, and the Office of Juvenile Justice and Delinquency Prevention emphasize the importance of risk and need assessment tools to ensure proper placements and dispositions for juvenile offenders (Leiber & Boggess, ; Vincent et al., ). The risk–need–responsivity (RNR) framework that guides most community correction programs emphasizes the importance of taking criminogenic needs and individual characteristics into account when designing rehabilitation plans for juvenile offenders that could influence responsivity to treatment (Andrews & Bonta, , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, individuals with lighter skin tones appeared to have an increased likelihood of having their probation revoked. While there are disparities in who gets violated, Leiber and Boggess (2012) and Bechtold, Monahan, Wakefield, and Cauffman (2015) showed that minorities were no more likely to receive a more punitive outcome after a probation violation than their White counterparts.…”
Section: Racial Equity In Community Supervisionmentioning
confidence: 96%
“…As stated previously in the text, one of the purposes of these risk/needs assessment instruments is to produce more equitable treatment of minority youth in juvenile court proceedings. While some prior research has shown that the use of such tools may reduce racial/ethnic bias in decision making, other studies indicate that racial/ethnic effects to the disadvantage of minority youth still emerge (Leiber & Boggess, 2012; Maggard, 2015). Recall that in the present research, racial/ethnic effects were found even after controlling for the year of the referral and corresponding urban/rural distinction.…”
mentioning
confidence: 99%